Mitral Valve Replacement and Subaortic Membrane Resection Following Pneumonectomy - Melih Hulusi Us; Murat Ugurlucan; Murat Basaran; Ozer Selimoglu; Ali Kocailik (Case Reports in Medicine)
The pulmonary status is a vital factor for patients undergoing open heart surgery. The cardiac surgery itself deteriorates the actual pulmonary functions. Today, patients are no longer living with a cardiac disease due to compromised respiratory functions secondary to various pathologies, patients with lung disorders more often seek solutions for their cardiac disease and they are commonly operated. However, the resection of a lobe or a whole lung is a major challenge for the patients planned for cardiac surgery. In this report, we present a 65-year-old patient, who had left pnemonectomy which had been performed 8 years ago and was admitted for mitral valve replacement and subaortic membrane resection.